2019
DOI: 10.1002/uog.20114
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome of monochorionic twin pregnancy complicated by selective fetal growth restriction according to management: systematic review and meta‐analysis

Abstract: Type I sFGR is characterized by good perinatal outcome with expectant management, which represents the most reasonable management strategy for the large majority of affected cases. Pregnancies complicated by Type II and III sFGR treated with fetoscopic laser ablation had higher mortality but lower morbidity compared to those managed expectantly, supporting the use of fetal therapy at gestations remote from neonatal viability - with scarce data on outcome following selective reduction. However, in view of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 34 publications
3
73
0
9
Order By: Relevance
“…According to a recent systematic review, expectant management is appropriate in most cases of Type I sFGR. For Types II and III sFGR diagnosed before 24 weeks, fetal therapy may contribute to higher mortality with lower morbidity of the surviving twin. Although perinatal mortality in multiple pregnancy seems to be decreasing, the rate of stillbirth is still much higher compared with that in singletons.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent systematic review, expectant management is appropriate in most cases of Type I sFGR. For Types II and III sFGR diagnosed before 24 weeks, fetal therapy may contribute to higher mortality with lower morbidity of the surviving twin. Although perinatal mortality in multiple pregnancy seems to be decreasing, the rate of stillbirth is still much higher compared with that in singletons.…”
Section: Discussionmentioning
confidence: 99%
“…The management of SIUGR remains controversial [30]. Our original pilot study showed that laser ablation of the placental vascular anastomoses in SIUGR patients was possible [1].…”
Section: Discussionmentioning
confidence: 99%
“…MC pregnancies can be complicated by selective fetal growth restriction (sFGR) due to unequal placental share, twin-twin transfusion syndrome (TTTS), and twin Gabby/Chon/Korst/Llanes/Chmait Fetal Diagn Ther 2020;47:817-823 818 DOI: 10.1159/000509401 anemia polycythemia sequence due to unequal sharing of blood through placental vascular communications, and potentially lethal discordant anomalies [1][2][3]. These complications increase the risk of perinatal morbidity and mortality [4][5][6][7][8][9][10]. In the event of fetal demise of one twin, the co-twin has an increased risk of neurological morbidity and death [11][12][13].…”
Section: Introductionmentioning
confidence: 99%